Analysis of futures trading on the Binance platform from the perspective of Fiqh Muamalah - Zulkarnain , Rifki; Syibly, M. Roem (Universitas Islam Indonesia, 2024)
IntroductionOne of the business transactions that developed in the digital era is futures trading. This type of transaction involves high risk where profit is obtained from the difference between buying and selling, with goods being delivered at a later date. Profits are obtained from price fluctuations on traded commodities. This type of futures trading is also done on the Binance platform. Many traders are interested in this type of trade but do not have sufficient knowledge and understanding, especially regarding Fiqh legality.ObjectivesThe study aims to explain the practice of futures trading on the Binance platform from the perspective of Fiqh Muamalah. MethodThis study is literature research with a juridical-normative approach that relates facts to futures trading cases.ResultsThe results of this study explain that futures trading on the Binance platform includes bay' al-şarf, a type of money trade in which money is obtained and delivered at a later date. ImplicationsFutures trading on the Binance platform in Fiqh Muamalah is prohibited because it involves elements of uncertainty (gharar) and speculation (maysir). The exchange rate is uncertain, which can cause one party to benefit and the other party to be harmed.Originality/NoveltyThis research contributes to the theory of Fiqh legality in future trading practices.